Diversified Production of Recycled Aggregate Concrete Mixture with the Addition of Single and Hybrid Fibers - Ismail, Sallehan; Nur Syazwani Wan Mohammad, Wan; Ramli, Mahyuddin (International Journal of Engineering and Technology, 2018)
The low strength property of recycled concrete aggregates (RCAs) limits its widespread application in the production of high-strength recycled aggregate concrete (RAC). In this study, RCA properties were improved prior to its incorporation into an RAC mixture through surface treatment. This mixture was subsequently diversified considering the benefits of adding various fiber-reinforced systems to enhance RAC performance. Two types of short discrete synthetic fibers, namely, polyolefin and polypropylene, were added in single and hybrid forms. This study aimed to investigate the effectiveness of the diversified modification of RAC mixture production on the mechanical strength of the resulting RAC. Various properties of the modified RAC were analyzed. Although the modified RAC mixture using treated RCA significantly enhanced the mechanical strength of this RAC, the diversification of the RAC mixture with additional polyolefin and polypropylene fibers, particularly in the hybrid form, further optimized the RAC performance.Â